Synthesis and Structural Characterization of Y-doped Pyramidal ZnO Powders - Kebiroğlu, Mehmet Hanifi; Kaygılı, Omer; Bulut, Niyazi; Okur, H. Esma; Ercan, Ismail; Ercan, Filiz Altıparmak; İnce, Turan (My University, 2020)
The present study focuses on the structural changes in ZnO powder induced by doping of a rare earth metal of Y.For this aim, we synthesized four ZnO samples with different Y-content using the combustion reaction method.X-ray powder diffraction (XRPD) technique and scanning electron microscopy (SEM) results confirm that the asinvestigated structural parameters and morphology of the ZnO structure were affected directly by the concentrationof Y dopant. For each Y-doped sample, randomly-oriented pyramidal morphology and the formation of a minorityphase of Y2O3 were observed. A gradual increase in both lattice parameters and unit cell volume was detected withincreasing Y content. All samples were found to be thermally stable in the temperature interval of 25-950 °C.
Keywords: Mühendislik; Kimya; Malzeme Bilimleri; Seramik